2018
DOI: 10.4103/ijpsym.ijpsym_558_17
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Craving and Early Relapse in Alcohol Dependence: A Short-Term Follow-up Study

Abstract: Background: The role of craving in alcohol dependence and its relationship with relapse has been studied widely in the past decade. The present study was undertaken to assess the role of craving in short-term relapse of patients seeking treatment for alcohol dependence and changes in craving score at the end of detoxification and at follow-up. Materials and Methods: A total of 34 male individuals with alcohol dependence (excluding comorbid drug dependence, organic or ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…The present follow-up study aimed to assess the principal factors that influence the treatment outcome, follow-up, and abstinence rates among patients with alcohol use disorder at the time of admission and three months post-discharge. The follow-up duration was taken as three months due to the reasons such as: a) published literature from similar demographic zones which revealed 85% of patients with alcohol use disorder relapsed by 3 months, b) a short follow-up period to ensure the maximum number of participants in the follow-up and to minimize attrition, and c) to minimize logistic difficulties in sustaining long follow-up periods due to COVID-related movement restrictions encountered by the study participants [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The present follow-up study aimed to assess the principal factors that influence the treatment outcome, follow-up, and abstinence rates among patients with alcohol use disorder at the time of admission and three months post-discharge. The follow-up duration was taken as three months due to the reasons such as: a) published literature from similar demographic zones which revealed 85% of patients with alcohol use disorder relapsed by 3 months, b) a short follow-up period to ensure the maximum number of participants in the follow-up and to minimize attrition, and c) to minimize logistic difficulties in sustaining long follow-up periods due to COVID-related movement restrictions encountered by the study participants [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated the role of coping in predicting the risk of lapse and relapse, and improvement of coping skills to reduce the risk of relapse to alcohol [22,23]. Higher craving also predicted a higher risk of relapse on alcohol [24]. Finally, all three factors, craving, coping and level of motivation, may interact with each other and influence the propensity of relapse‐ as per the reformulated cognitive‐behaviour model or dynamic model of relapse [25].…”
Section: Discussionmentioning
confidence: 99%
“…In substances with similar effects to inhalants, such as alcohol, subjects have significantly high craving scores (Kharb, Shekhawat, Beniwal, Bhatia, & Deshpande, 2018;Petit et al, 2017). Literature points out that people who have a low inhibitory control will be more prone to use substances and therefore engage in drug seeking behaviors in the presence of craving (Bresin & Verona, 2019).…”
Section: Discussionmentioning
confidence: 99%